2007
DOI: 10.1007/s00414-006-0121-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical forensic radiology in strangulation victims: forensic expertise based on magnetic resonance imaging (MRI) findings

Abstract: Based on only one objective and several subjective signs, the forensic classification of strangulation incidents concerning their life-threatening quality can be problematic. Reflecting that it is almost impossible to detect internal injuries of the neck with the standard forensic external examination, we examined 14 persons who have survived manual and ligature strangulation or forearm choke holds using MRI technique (1.5-T scanner). Two clinical radiologists evaluated the neck findings independently. The dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 15 publications
3
71
1
4
Order By: Relevance
“…Furthermore, by knowing these postmortem findings, it is even possible to use whole-body MRI in clinical forensic medicine where noninvasive and non-radiation examination of a living accident victim and other living persons [17] is highly beneficial and especially when reconstructive questions are open.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by knowing these postmortem findings, it is even possible to use whole-body MRI in clinical forensic medicine where noninvasive and non-radiation examination of a living accident victim and other living persons [17] is highly beneficial and especially when reconstructive questions are open.…”
Section: Discussionmentioning
confidence: 99%
“…Intra-, subcutaneous, intramuscular, perilaryngeal and parapharyngeal oedema or haemorrhage were defined as diffuse areas of TIRM or T2 hyperintensity and T1 hypo-or hyperintensity. Special attention was paid to the platysma, since involvement of the platysma was suspected to be a specific sign of strangulation by Yen et al [5,11], but the sternocleidomastoid, strap and dorsal neck muscles were assessed together. The platysma muscle was considered affected when it was thickened or hyperintense on the TIRM or T2-weighted sequence.…”
Section: Mr Image Analysismentioning
confidence: 99%
“…MRI allows for better assessment of the inner structures of the neck, like soft tissue, vessels and larynx that cannot be clinically examined or documented. Yen et al [11] investigated 14 survivors of manual strangulation with MRI and found typical strangulation signs such as subcutaneous and intramuscular haemorrhage (platysma), haemorrhage of lymph nodes and salivary glands, but few injuries in the larynx and hyoid, which is more typical on post-mortem MRI, CT or autopsy. To our knowledge, no radiological sign was ever classified as lifethreatening in survivors of strangulation.…”
Section: Introductionmentioning
confidence: 99%
“…PMMR finds its place in research of neurological lesions (12,13), as well as the spinal cord, especially in the cervical region (14). Contrast resolution of MRI is valuable in characterizing fluid effusions, especially blood-containing ones (15) and solid organ injuries.…”
Section: Considerations Common To the Whole Field Of Post-mortem Imagingmentioning
confidence: 99%